(untitled) (World Science, 2021)
Malocclusions that have not been eliminated in time can cause complications such as periodontal diseases, TMJ and muscle dysfunctions. An objective indicator of functional disorders is the change of bioelectrical activity of masticatory muscles. The aim of our study was to estimate the functional state of maxillodental system in order to develop the individualized treatment and achievement of high functional and aesthetic optimum in patients with associated occlusal abnormalities who need complex treatment. All examined patients had deviations of the average amplitude of bioelectrical activity of muscles, asymmetry in muscle function, bursts of spontaneous bioelectrical activity at rest, chewing cycle fragmentations, changes in rest and activity ratio during chewing. One of the most important criteria for the transition to the next stage of treatment is normalization of bioelectrical activity of the muscles. Such approach allows to achieve stable and long-lasting functional results of the treatment.